2022
DOI: 10.3389/fonc.2022.939343
|View full text |Cite
|
Sign up to set email alerts
|

A real-world study of anlotinib as third-line or above therapy in patients with her-2 negative metastatic breast cancer

Abstract: BackgroundAntiangiogenic agents provides an optional treatment strategy for patients with metastatic breast cancer. The present study was conducted to evaluate the efficacy and safety of anlotinib as third-line or above therapy for patients with HER-2 negative metastatic breast cancer.MethodsPatients with HER-2 negative metastatic breast cancer who have failed from prior therapy and treated with anlotinib monotherapy or combined with chemotherapy or immunotherapy from June 2018 to December 2020 were retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 36 publications
2
8
0
Order By: Relevance
“…was similar to that in previous relevant clinical trials (34,35). Antiangiogenic drugs likely to increase the probability of hemorrhage.…”
Section: Secondary Endpoints and Other Best Clinical Responsesupporting
confidence: 88%
See 3 more Smart Citations
“…was similar to that in previous relevant clinical trials (34,35). Antiangiogenic drugs likely to increase the probability of hemorrhage.…”
Section: Secondary Endpoints and Other Best Clinical Responsesupporting
confidence: 88%
“…In a real-world study of anlotinib monotherapy or combined with chemotherapy in multi-line therapy in patients with advanced breast cancer, the median PFS of monotherapy was 3.0 months, and that of combined treatment was 5.5 months. In subgroup analysis, the median PFS of TNBC patients was 3.5 months ( 35 ). In our study, the median PFS of TNBC patients who had previously received at least two lines of treatment in the metastatic setting was 5.0 months, which was longer than that of patients with metastatic TNBC reported by Hu et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most common AEs related to nervous system disorder was reported to be headache (33 [11.2%]) in the ALTER0303 trial ( Han et al, 2018 ). In addition, there were a few rare AEs reported such as insomnia, sensory neurotoxicity, and seizure ( Huang et al, 2021 ; Liu et al, 2021 ; Lu et al, 2022 ; Nie et al, 2022 ; Shao et al, 2022 ; Zou et al, 2022 ). Although a few cases of posterior reversible encephalopathy syndrome (PRES) caused by some anti-angiogenic drugs were reported in the literature ( Koopman et al, 2008 ; Chelis et al, 2012 ; Myint et al, 2014 ; Sharma et al, 2016 ; Saraceno et al, 2017 ; Miaris et al, 2019 ; Van Pelt et al, 2020 ), no PRES has been previously reported in SCLC patients treated with anlotinib.…”
Section: Introductionmentioning
confidence: 99%